Integrating Electrochemistry Into Bioreactors: Effect of the Upgrade Kit on Mass Transfer, Mixing Time and Sterilizability - Rosa, Luis F. M.; Hunger, Steffi; Zschernitz, Tom; Strehlitz, Beate; Harnisch, Falk (Frontiers in Energy Research, 2019)
Microbial electrosynthesis (MES) is an exciting and dynamic research area at the nexus of microbiology and electrochemistry. To pave the way of MES to application, reactor infrastructure is needed that meets the requirements of both biological, and electrochemical engineering. Recently we presented an upgrade kit facilitating turning commercial bioreactors based on batch stirred tank reactors (BSTR) into electrobioreactors that can be scaled and benchmarked. The upgrade kit comprises electrodes and an inlay with membrane, separating the BSTR chamber into anode and cathode compartments. The obtained electrobioreactors enable seizing the existing infrastructure for monitoring and controlling the bioprocess while being complemented by electrochemical control and measurement. Here the effect of the upgrade kit on mass transfer was investigated in a 1 L electrobioreactor using experimental approaches and modeling of fluid dynamics. It is shown that the fluid dynamics in the BSTR are changed dramatically, impacting the integral parameters volumetric mass transfer coefficient, kLa, and mixing time, θ. The influences of the inlay chamber and electrodes as well as stirrer position and geometry are described. Additionally, the sterilizability of the inlay, housing the polymer-based membrane of the electrobioreactor, which is needed for operating two-chamber MES based on microbial pure cultures, are demonstrated.